1998
DOI: 10.1111/j.1399-6576.1998.tb05137.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of patient variables on sensory level after spinal 0.5% plain bupivacaine

Abstract: Multiple regression analysis revealed that age, weight, and height significantly correlated with the sensory level after subarachnoid injection of plain bupivacaine. The low predictive value suggests that patient factors other than age, weight, or height add to cephalad spread of SA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 20 publications
2
17
1
1
Order By: Relevance
“…Dorso‐sacral distance and cerebrospinal fluid volume are positively correlated and there would be less lumbosacral cerebrospinal fluid volume in patients with greater dorso‐sacral distance. The other three physical characteristics – volunteers’ age, height and weight – were found to have little correlation with lumbosacral cerebrospinal fluid volume in this study, which could explain the results of many previous studies . Hogan, Q. H. et al and Sullivan, J. T. et al reported that lumbosacral cerebrospinal fluid volume was inversely proportional to BMI, but the correlation coefficient was relatively low.…”
Section: Discussioncontrasting
confidence: 71%
“…Dorso‐sacral distance and cerebrospinal fluid volume are positively correlated and there would be less lumbosacral cerebrospinal fluid volume in patients with greater dorso‐sacral distance. The other three physical characteristics – volunteers’ age, height and weight – were found to have little correlation with lumbosacral cerebrospinal fluid volume in this study, which could explain the results of many previous studies . Hogan, Q. H. et al and Sullivan, J. T. et al reported that lumbosacral cerebrospinal fluid volume was inversely proportional to BMI, but the correlation coefficient was relatively low.…”
Section: Discussioncontrasting
confidence: 71%
“…Similar to the results of the current study, several studies in non-pregnant adults found increased BMI was associated with a higher cephalad sensory level when local anesthetic solutions were administered at doses necessary for surgical anesthesia. [7][8][9][10][11] There was a large variability in cephalad sensory levels following intrathecal injection of a hypobaric solution in the current study, similar to studies of isobaric and hyperbaric solutions. There have been several small series of case reports in which parturients had sensory blockade of cranial nerves after initiation of CSE analgesia.…”
Section: Objectif : Déterminer Si L'étendue Du Blocage Sensitif Suivsupporting
confidence: 63%
“…This level of association between the primary outcome variable (cephalad sensory spread) and height, weight, and BMI was similar to that observed in a study of the influence of body habitus and sensory spread after the intrathecal injection of isobaric bupivacaine. 7 Pearson's correlations and linear regression were used to determine the association between height, weight, BMI and the cephalad sensory level. The right vs left sensory levels were compared using the Wilcoxon signed ranks test.…”
Section: Objectif : Déterminer Si L'étendue Du Blocage Sensitif Suivmentioning
confidence: 99%
“…Mas deve ser salientado que a determinação clí-nica do local de punção está errada em mais de 50% dos casos e em geral ocorrendo em nível mais alto do que o considerado 10 . Diferenças anatômicas individuais, identificadas por exame de ressonância magnética, tem sido responsabilizadas como causa de falha da raquianestesia com soluções hiperbáricas 11 . Pacientes grávidas a termo têm densidade de LCR mais baixa que a população geral, variando de 1,00030 ± 0,00004 g.ml -1…”
Section: Discussionunclassified
“…But it should be highlighted that clinical puncture site determination is wrong in more than 50% of cases, and in general it is located at a higher level than the one that is being considered 10 . Individual anatomical variations identified by MRI have been charged as responsible for spinal anesthetic failures with hyperbaric solutions 11 . Term pregnant patients exhibit lower CSF density as compared to general population, around from 1.00030 ± 0.00004 g.ml -1 , due to hormonal factors, such as increased estrogen and progesterone concentrations 9, 12,13 .…”
Section: Discussionmentioning
confidence: 99%